The Importance of English in the Era of Globalization for MI/SD Children - Pamesti, Bunga Roro; Rambe, Indah Aulia; Nasution, Abdillah; Syahfitri, Nur Indah; Amirul, Bani (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
English is one of the languages of communication used all over the world. Up-to-date information in the fields of science, technology, politics, education, health, economics, and other fields is always written in foreign languages, especially English. In the era of globalization and free markets, all individuals must be able to compete for reliable resources. The role of English is so important that learning English should be an individual investment to achieve a bright life. But in reality, there are still many students, especially EFL learners, who have difficulty understanding English due to a lack of practice in daily life. Objectives: To help students understand the importance of learning English in the era of globalization and provide opportunities to participate in English language training